Metodologia para realização de projeto de fornecimento de energia elétrica para iluminação pública - Araújo, Aline Moreira de (2022)
The quality of municipal lighting systems directly interferes with society's quality of life, besides being a relevant part of crime prevention. Therefore, making and executing an efficient project is a fundamental factor that guarantees the quality of the service and prominence in the job market. This study presents the main stages necessary to elaborate a municipal lighting project, demonstrating and detailing the concepts and equipment that make up a municipal lighting system through the standards of the Brazilian Association of Technical Standards (ABNT) n°. 5101/2018 and 15129/2012, by the technical notes of Equatorial Piauí n°. 005, 008 and 023, as well as the stages of recognition of the work site, classification of roads, lighting characteristics, topology, measurement, protection, feasibility study, project presentation, project analysis, project execution, inspection and connection of the project.. Thus, to validate the information presented in this work, a case study was carried out detailing the steps to carry out a municipal lighting project. It concluded that for a public lighting project in the state of Piauí, steps are needed that aim to provide the realization of a project that guarantees quality lighting efficiency based on strict standards and technical notes.